Management of Pain, Mobilization, and Pressure Injuries in Complex Revision Arthroplasty: A Multidisciplinary Case Report - Sümeyye Kuzucu; Mehmet Musa Emir; Sevil Güler; Durmus Ali Ocguder (Journal of Gazi University Health Sciences Institute, 2026)
Complex revision arthroplasties are indicated particularly in cases of severe bone loss, aseptic loosening, periprosthetic infection, and recurrent instability. Revision total hip arthroplasty is associated with higher complication rates and greater functional limitations than primary surgery. This study aimed to evaluate the effects of a multidisciplinary approach on pain, mobilization, and pressure injury following revision hip arthroplasty in a high-risk patient. The case involved a 75-year-old patient with a history of multiple partial hip arthroplasties and revision procedures. Preoperative assessment revealed acetabular protrusion and femoral and pelvic bone defects. Pelvic reconstruction was performed using an ilioischial cage, a distally fixed femoral stem, and a constrained liner to address instability. Postoperative care was provided by a multidisciplinary team consisting of orthopedic surgeons, an orthopedic nurse, and a physiotherapist. Management included hemodynamic stabilization, pain control, thromboembolism prophylaxis, pressure injury monitoring, and early mobilization. The patient's Visual Analog Scale (VAS) pain score decreased from 7–9 during the first week to 1–3 by the fifth week. Mobilization progressed from complete bed dependence to short-distance ambulation. A pre-existing Stage 2 pressure injury progressed to Stage 3 postoperatively but improved to Stage 2 after appropriate wound care. Although complete independent ambulation was limited by neurological deficits and advanced age, functional improvement was achieved. This case highlights the importance of a multidisciplinary approach, close follow-up, and patient education in improving outcomes and facilitating early rehabilitation after complex revision hip arthroplasty.